Measuring patient satisfaction with mental health services in correctional settings: a systematic scoping review - Roland M. Jones; Roland M. Jones; Niroshini Mather; M. Umer Waqar; Madleina Manetsch; Chloe Taylor; Vito Adamo; Marco Kilada; Cory Gerritsen; Cory Gerritsen; Alexander I. F. Simpson; Alexander I. F. Simpson (Frontiers in Psychiatry)
IntroductionThe measurement of patient satisfaction with mental health services is well-established and a key indicator of performance. Patient satisfaction with mental health services received in criminal justice settings however is however less frequently studied. Our aim was to establish how frequently patient satisfaction with mental health services in correctional (prison) settings is being reported, and to identify methods of measurement including all tools that have been used to measure patient satisfaction in these settings.MethodsA comprehensive search of published articles and thesis dissertations was undertaken using multiple databases. Two reviewers independently screened the references to determine eligibility and then extracted the necessary data using a predefined extraction template. Only studies that measured patient satisfaction with a mental health service or intervention within a correctional facility were included.Results46 studies, which included various measures, were identified as being eligible for inclusion. The median number of patients involved in these studies was 37.5 (range: 4–1150). Tools were heterogeneous in length, purpose, and design, and these measured a variety of different domains. Most of the tools used had been developed in non-correctional settings and applied in correctional settings without adaptation. Tools with established psychometric properties were used only in ten instances, whereas the majority of the studies reported using author-developed interviews and questionnaires to obtain feedback.ConclusionPatient satisfaction measurement tools in correctional services are heterogeneous and largely unvalidated; there is no uniformity in the measurement methods used.Systematic Review Registrationhttps://osf.io/md8vp, identifier md8vp.